Gagauz Identity in the Post-Soviet Period - Nesibe Ayşe Sağlam; Yusuf Adıgüzel (Journal of Economy Culture and Society)
The article covers how the reproduction and reconstruction of the Gagauz identity occurs in the Autonomous Territorial Unit of Gagauzia within Moldova in the Post-Soviet period, which institutions and practices were involved in this process and how identity was transmitted to new generations. The article also explores how individuals live, maintain and pass down their ethnic identity through media practices and socialisation areas like family, school, church where daily lives are spent. In-depth interviews were conducted with 28 people in April-May 2018 in the Gagauz Autonomous Region via the ethnographic technique. Our findings revealed that the Gagauzi lived, constructed and transmitted their ethnic identities in a “limited” rather than holistic way in their socialisation practices. Contrary to expectations, there is clear evidence that the Gagauz identity has begun to erode rather than strengthen in the post-autonomy period. We found their perception of Russian as their mother tongue besides their ethnic language has weakened Gagauz and the proliferation of mixed marriages leads to an erosion in their ethnic identity. The Gagauz identity, which has become more vulnerable and open to global influences, has ceased to be stationary and localised, but has begun to be reshaped by global conditions in line with transnational mobility.